Comparative Investigation of Thyroid Autoantibodies Between Type 1 and Type 2 Diabetes Mellitus Patients in Baghdad City - Al-Jowari, Suha A. (Iraqi Journal of Science, 2022)
The level of thyroid autoantibodies between type 1 and type 2 diabetes mellituspatients in Baghdad City were investigated.Fifty individuals (25 female and 25 male) with type-1 DM in the age group of 10to 35 years and seventy (35 female and 35 male) of having type-2 DM in the agegroup of 33 to 60 years were investigated. A control group of twenty-five nondiabeteswas included. Serum sample collected was used to estimate anti-TPO, TGand thyroid stimulating hormone antibodies (thyroid stimulating immunoglobulinTSI and thyrotropin binding inhibitory immunoglobulin TBII) by using enzymelinkedimmunosorbent assay (ELISA) technique.The results show that there is a significant (p< 0.05) increase in the level ofthyroid peroxidase antibody (TPO-Ab) in female patients with T1DM and T2Mcompared with control non-diabetes group. Furthermore, there is no significant (p<0.05) difference in the level of TPO-Ab and Tg-Ab in male patients with T1DM andT2DM compared with non-diabetes group. The results of this study also demonstratethat there is a significant (p< 0.05) increase in the level of thyroid stimulatingimmunoglobulin (TSI) in male patients with T1DM compared with control nondiabetesgroup. In addition, there is no significant (p< 0.05) difference in the level ofTSI in female patients with T1DM and male and female with T2DM compared withnon-diabetes group. These results also illustrate that there is significant (p< 0.05)increase in the level of thyrotropin binding inhibitory immunoglobulin (TBII) infemale and male patients with T2DM compared with control non-diabetes group.Furthermore, there is no significant (p< 0.05) difference in the level of TSI infemale and male patients with T1DM compared with non-diabetes group.From this study, it concluded that the presence of antithyroid peroxidase (TPO)antibodies is helpful in predicting the development of autoimmune thyroid disorders,especially hypothyroidism. Subclinical hypothyroidism has a negative influence onlipid metabolism and it is an independent risk factor for myocardial infarction.